2019
DOI: 10.1016/j.jaip.2018.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes of Recurrent Wheezing in Preschool Children: Identification by Latent Class Analysis and Utility in Prediction of Future Exacerbation

Abstract: Background-Recurrent preschool wheezing is a heterogeneous disorder with significant morbidity, yet little is known about phenotypic determinants and their impact on clinical outcomes. Objective-Latent class analysis (LCA) was used to identify latent classes of recurrent preschool wheeze and their association with future exacerbations and inhaled corticosteroid (ICS) treatment response. Methods-Data from five clinical trials of 1,708 children age 12-71 months with recurrent wheezing were merged. LCA was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 54 publications
1
43
1
1
Order By: Relevance
“…subgroups: (a) a food and environmentally sensitized group, representative of the classical progression of the atopic march; (b) an environmentally sensitized group; and (c) a nonsensitized group (Figure 2). These data are consistent with reports that the nonsensitized group tends to be less responsive to standard corticosteroid asthma medications 8. Specifically, these reports are from the high-risk CAPS and MACS studies from Australia and the population-based LISAplus study from Germany 6,7.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…subgroups: (a) a food and environmentally sensitized group, representative of the classical progression of the atopic march; (b) an environmentally sensitized group; and (c) a nonsensitized group (Figure 2). These data are consistent with reports that the nonsensitized group tends to be less responsive to standard corticosteroid asthma medications 8. Specifically, these reports are from the high-risk CAPS and MACS studies from Australia and the population-based LISAplus study from Germany 6,7.…”
supporting
confidence: 90%
“…These data are consistent with reports that the nonsensitized group tends to be less responsive to standard corticosteroid asthma medications. 8 In conclusion, we provide data describing a potentially highrisk preschool asthma cohort in Canada using a comprehensive approach capturing sensitization to allergens of paramount importance. By applying both allergen extracts and components, we identified that peanut and animal allergens from cat and dog were major allergen sources in this North American cohort of preschool asthmatics.…”
Section: (Canadian Healthy Infant Longitudinal Development Study [Chimentioning
confidence: 99%
See 1 more Smart Citation
“…However, decreased symptoms and medication use can be considered as a surrogate for asthma control . The decrease in specific AHR might lead to less allergen‐driven asthma exacerbations . Of note, the number of studies that demonstrated a significant effect on the early and, most importantly, the late phase of allergen‐induced bronchial reaction is very limited. There is limited evidence on potential direct or indirect cost‐saving effect by adding HDM SCIT to regular asthma treatment. Asthma control and lung function should be assessed regularly (preferably before each SCIT injection); a minimum 30 minutes of observation after therapy at the office is recommended; SCIT should be administered by healthcare professionals (HCPs) with proper training in AIT, under proper conditions to manage severe bronchospasm or a systemic anaphylactic reaction.…”
Section: Recommendationsmentioning
confidence: 99%
“…Second, although several studies, such as that by Oksel et al, 3 have focused only on lung function variables, others have also included other observable clinical features, such as symptoms and allergic sensitization variables in the phenotype identification models. 6,7 There is currently no consensus on which approach is best for the purpose of personalized care delivery. Indeed, some have argued that a phenotype might or might not be associated with an underlying disease mechanism but provides an opportunity for application of personalized therapy (eg, a patient with persistently low lung function despite therapy attempts).…”
mentioning
confidence: 99%